Significance of thermal radiation on 3D thermo-bioconvection flow of trihybrid nanofluid with thermophoresis and electrophoresis - Galal, Ahmed M.; Becheikh, Nidhal; Elaissi, Samira; Rashid, Rzgar Farooq; Kanwal, Humaira; Bettaieb, Boutheyna Belhaj; Abbas, Munawar; Khan, Ilyas; Garalleh, Hakim A.L. (Journal of radiation research and applied sciences, 2025)
This research examined the effects of thermal radiation on Darcy-Forchheimer flow of trihybrid nanofluid over an inclined rotating disk with thermophoresis and electrophoresis. By controlling fluid flow enabled by gravity and viscous forces, gyrotactic and oxytactic microbes improve heat and mass transmission in energy systems. Improved medication delivery, cooling systems, and biofilm control are just a few of the uses for trihybrid nanofluids, which blend these microbes and nanoparticles to increase thermal conductivity and stability. When improved thermal conductivity and energy transmission are essential, it can be used in the construction of microfluidic devices, and effective heat exchangers. The current study has investigated the analysis of thermophoretic and electrophoretic particle deposition in radiative flow of a tri-hybrid nanofluid across an inclined rotating disk with bioconvection. Mathematical solutions to the appropriately modified main equations have been found using the Bvp4c approach. The profile of oxytactic microbe significantly decreases as the oxytactic microbe Schmidt number increases. The solutal profile falls as the electrophoretic parameter rises, whereas the thermophoretic parameter exhibits the opposite tendency. It's amazing how much more of an impact the Yamada-Ota ternary hybrid nanofluid model makes than the Hamilton Crosser model.